The effects of acute antioxidant supplementation on aerobic capacity and high intensity training - Collins, M. B. (Medicine & Science in Sports & Exercise, 1998)
The effects of acute antioxidant supplementation on maximal aerobic power following three successive days of high intensity interval training were examined. Trained male cyclists (N = 20) performed VO2max tests and training sessions on an electronically-braked ergometer. Antioxidants ingested over five days were vitamins C and E, beta-carotene, and coenzyme Q10. Relative VO2 improved for the antioxidant but not for the placebo group between pre- and posttests. The antioxidant group improved work rate over time. Implication. Athletes who incorporate high intensity training as part of normal training can do more intense training closer to competitions without negative effects on performance if they are fed acute antioxidant supplements.